(untitled) (Global Journal of Management and Business Research, 2016)
The public transport sector in Tunisia has experienced economic, social and financial difficulties. The declining of the revenue shortfalls and the increased of public expenditure are the critical observed phenomenon. Our research is meant to discover the weaknesses, to find a practical solution and to improve the performance of the public transport sector by improving the performance of regional urban operators. For this reason, we have developed a model of performance that which ensures the comparisons between different operators working in similar conditions. This step is running by method of multi-criteria decision, appointed, Evidential Reasoning Approach (ER). This approach is proposed to deal with uncertain decision knowledge in multiple-attribute decision making (MADM) problems with both quantitative and qualitative attributes under uncertainties.